Natural Selection at New College: The Evolution of Science and Theology at a Scottish Presbyterian Seminary - Harris, Mark (Zygon, 2022)
The contemporary creation–evolution debate has become so polarized (over the issue of either Genesis or evolutionary science) as to obscure the more nuanced questions that have arisen in the historical and theological reception of Darwinism. Edinburgh's New College has been the academic home to some prominent scientists and theologians who have grappled with these questions since the early days of evolutionary science in the first half of the nineteenth century. Most obviously, this activity was focused on the decision to create a Chair in Natural Science in 1845, which would be occupied by a recognized scientist. The Chair became “extinct” in the 1930s, but in between times, its holders made important theological assessments of evolution along the way. This article outlines the contributions made by the individuals who occupied this Chair, as well as more recent figures in the evolution of science and theology at New College.